House prices in the measurement of inflation: an application using Irish data - O'Sullivan, Roisin (Economic & Social Studies, 2005)
This paper illustrates the impact on Irish inflation of including a house-price series with the current components of the harmonised index of consumer prices (HICP). We construct a dynamic factor index of inflation that weights the individual price series according to the strength of their signal about the common trend in prices. As the relatively noisy house-price series attracts a weight of only 3 per cent in the index, the inclusion of house prices in this way does not hugely alter the recent pattern of inflation for Ireland, despite house prices exhibiting much stronger growth on average than the current measure of consumer prices.
Keywords: Housing markets; Inflation; Ireland; House prices